Production and Application of Keratinase Enzyme from 4 Strains of Bacillus spp. Isolated from Yogyakarta and Garut City - Wandita, Theresia Galuh (2015)
Processing of waste chicken feathers can be used as a biological treatment with keratinase enzyme. Keratinase enzyme can be produced by microorganisms. Keratinase enzyme expected to be produced from Bacillus spp. which has been previously isolated from Yogyakarta and Garut City. The purpose of this research was to determine the production of keratinase enzyme produced from Bacillus spp. and apply the keratinase enzyme in the process of degradation of chicken feathers. Research consists to measuring the growth of Bacillus spp. and investigation of degradation of chicken feathers by Bacillus spp. were analyzed descriptively, while data of digested protein by Bacillus spp. analyzed using a split plot design, if there are differences followed by Duncan New Multiple Range Test (DMRT). The results obtained bacterial growth and the ability of degradation was found on Bacillus sp. TD5B. Increasing of growth rate was followed by faster degradation time. Concentration soluble protein by Bacillus meganterium capable of producing higher compared with any others strains. Bacillus meganterium has had highest soluble protein (2,030 mg/ml). The longer degradation time followed by highest concentration soluble protein of feathers. The best incubation time at 8 hours that containing 2,256 mg/ml of soluble protein.